Analytical System Dynamics Modeling and Simulation - Fabien, Brian (Springer US : Imprint: Springer, 2009)
Analytical System Dynamics: Modeling and Simulation combines results from analytical mechanics and system dynamics to develop an approach to modeling constrained multidiscipline dynamic systems. This combination yields a modeling technique based on the energy method of Lagrange, which in turn, results in a set of differential-algebraic equations that are suitable for numerical integration. Using the modeling approach presented in this book enables one to model and simulate systems as diverse as a six-link, closed-loop mechanism or a transistor power amplifier. Drawing upon years of practical experience and using numerous examples and applications Brian Fabien discusses: Lagrange's equation of motion starting with the First Law of Thermodynamics, rather than the traditional Hamilton's principle Treatment of the kinematic/structural analysis of machines and mechanisms, as well as the structural analysis of electrical/fluid/thermal networks Various aspects of modeling and simulating dynamic systems using a Lagrangian approach with more than 125 worked examples Simulation results for various models developed using MATLAB Analytical System Dynamics: Modeling and Simulation will be of interest to students, researchers and practicing engineers who wish to use a multidisciplinary approach to dynamic systems incorporating material and examples from electrical systems, fluid systems and mixed technology systems that carries the derivation of differential equations to a final form that can be used for simulation.